Concentrations of Cu, Fe and Pb in Nerita lineata collected from selected sites in peninsular Malaysia and the snail's utility as a biomonitor of Pb - Cheng, Wan Hee; Yap, Chee Kong; Zakaria, Mohamad Pauzi; Aris, Ahmad Zaharin; Tan, Soon Guan (EM International, 2013)
The concentrations of Cu, Fe and Pb were determined in Nerita lineata snails and sediments collected from Selangor, Negeri Sembilan and Johore between May 2010 and April 2011. This study showed variations of heavy metal accumulations in shells, opercula and soft tissues. The mean concentrations (ug/g dry weight) of Cu, Fe and Pb were 5.00,29.97 and 50.07 for shells; 5.28, 19.50 and 49.34 for opercula; 14.94,539.25 and 18.83 for soft tissues, respectively. The mean total (pg/ g dry weight) concentrations of Cu, Fe and Pb in the surface sediments were 19.72,25956.14 and 46.99, respectively. Generally the results of this study were comparable with previous reports on the same species. The Pb levels of the snail samples were found to correlate well with the Pb levels in the sediments which confirmed the snail as a good biomonitor for Pb.